Metastasio on the British Stage 1728-1840 a catalogue - Burden, M (Routledge, 2007)
The libretti by the Viennese court poet Pietro Metastasio dominated the Continental and London music scenes for much of the 18th century; almost no composer worth his salt failed to set one of his texts at some stage, and by the end of the century, there were some 300 settings of the 27 operas alone. The smaller entertainments and the oratorios were similarly popular, and works in all of the genres became part of the London repertoire. The primary aim of this article is to provide a framework for the study of Metastasio on the stage in London, examining in precisely what form they reached the public and how the arias they contain became a resource for those working in the London theatres. It is also concerned with the extent of Metastasio’s influence in the theatre in Great Britain, and shows that Metastasio’s works could be located in nearly every theatre season and could be found in every publishing house and music shop. The picture that emerges is of a poet revered by the British public, and ever-present in the operas they saw and in the texts they read for over eighty years. The catalogue is divided into three main sections - I: Operas, II: Feste, Azioni, Componimenti, and III: Oratorios, and has four appendices. The first two deal entitled ‘Some Lost or Missing 18th-Century Metastasio printed libretti and texts for London’ and ‘Some Metastasio “London ghosts”’, The third, ‘Metastasio’s works in performance’ details season by season the number of performances of Metastasio’s works in London. The last, ‘Metastasio aria texts used in London in operas other than their original context’, provides a list of Metastasio arias which were re-employed in both other operas by Metastasio, or in works wholly unconnected with their original usage.